Hyers-Ulam stability of some positive linear operators - KAUR, Jaspreet; GOYAL, Meenu (Studia Universitatis Babeș-Bolyai Mathematica, 2025)
The present article deals with the Hyers-Ulam stability of positive linear operators in approximation theory. We discuss the HU-stability of Bernstein-Schurer type operators, Bernstein-Durrmeyer operators and find the HU-stability constant for these operators. Also, we show that the beta operators with Jacobi weights are HU-unstable. Mathematics Subject Classification (2010): 39B82, 41A35, 41A44. Received 04 December 2023; Accepted 23 October 2024.